Demography and migration : population trajectories from the Neolithic to the Iron Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France).: population trajectories from the Neolithic to the Iron Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). Sessions XXII-2 and XXIV-8 / Volume 5, (2020) - Unknown
No abstract available